A novel lignite-fired power plant integrated with a vacuum dryer: System design and thermodynamic analysis. (15th March 2015) - Liu, Ming; Wu, Dongyin; Xiao, Feng; Yan, JunJie
Abstract: Pre-drying of lignite before feeding to the boiler is a potential way to increase the net efficiency of lignite-fired power plants. Lignite pre-drying is, however, a high energy consumption process with a high risk of spontaneous ignition. If the lignite is dried at low temperature, the possibility of spontaneous ignition of lignite in the drying process could be lowed. Furthermore that low temperature energy could be used as the drying heating source may result in a high net efficiency of the power plant. Therefore, we designed a lignite-fired power plant integrated with a vacuum dryer. We also thermodynamically analyzed a reference case of a 1000 MW power plant by using theoretical models developed. The results show that the net efficiency of power plant can be increased by 2.39% or 1.88% absolutely, if a low-pressure steam or heat pump is used to provide the drying heat source, respectively. From analyzing main factors, we discovered that the net efficiency of the power plant increases with the drying degree and decreases with the operating pressure of the dryer, and the heat pump is a better choice to provide the heating source for drying purposes with its second-law efficiency higher than 0.76. Highlights: A novel lignite-fired power plant integrated with vacuum dryer was designed. The vacuum dryer was proposed to pre-dry lignite at low temperature. The net efficiency improvement of lignite-fired power plant was calculated with models developed. The influence of main factors on net efficiency of power plant was analyzed.